Zwischen Zuversicht und Sorge: Kindliche Autonomieentwicklung im Grenzbereich zu dissozialen Verhaltensweisen = Between confidence and concern : Development of child autonomy and the threshold to antisocial behavior - Schäfer, Christina Sandra; Schaefer, Jan-Christoph; Cierpka, Maximilian (Monatsschrift Kinderheilkunde, 2016)
Based on the pediatric development of autonomy, temper tantrums and aggressive behavior considered to be dimensional manifestations of early regulatory problems and the transition to oppositional defiant conduct disorders are described. Influencing factors, aspects of advice and treatment are presented. These deliberations are supplemented by knowledge from the results of current longitudinal studies on the psychosocial development of children with early externalized aggressive oppositional conduct problems up until adulthood.